An isotope dilution-liquid chromatography-tandem mass spectrometry-based candidate reference measurement procedure for the quantification of cortisol in human serum and plasma - Ott, Myriam; Singh, Neeraj; Bauland, Friederike; Köppl, Daniel; Kandler, Kerstin; Gaudl, Alexander; Geistanger, Andrea; Ceglarek, Uta; Rauh, Manfred; Geletneky, Christian; Taibon, Judith (Clinical Chemistry and Laboratory Medicine, 2025)
Accurate measurement of serum cortisol is crucial for the diagnosis and management of adrenal disorders. Thus, we have developed a novel isotope dilution-liquid chromatography-tandem mass spectrometry (ID-LC MS/MS)-based candidate reference measurement procedure (RMP) to quantify cortisol in human serum/plasma, offering higher sensitivity and reliability compared to existing RMPs. Quantitative Nuclear Magnetic Resonance spectroscopic (qNMR) methodology has been utilized to assign the absolute content (g/g) and SI-traceability to the reference materials. A novel two-dimensional heart-cut liquid chromatography (LC) approach was implemented for the LC-MS/MS, combined with a supported liquid extraction (SLE) sample preparation protocol. A multi-day validation experiment assessed precision and accuracy. Reproducibility was assessed by comparing procedure results between two independent laboratories, and measurement uncertainty (MU) was evaluated in compliance with current guidelines. The established RMP exhibited high sensitivity, with a quantification range of 0.800-600 » ng/mL (2.21-1,655 » nmol/L), exceeding the ranges of existing JCTLM-listed RMPs. Intermediate precision was ≤2.6 » %, and repeatability ranged from 0.9 to 1.9 » % across all concentration levels. The relative mean bias ranged from -1.3 to 1.4 » % for all matrices and concentration levels. Measurement uncertainties (MU) for cortisol in single measurements were ≤2.8 » % regardless of the concentration level and sample type. Using the certified International Federation of Clinical Chemistry and Laboratory Medicine (IFCC) reference panel, the equivalence between the candidate RMP and the Joint Committee on Traceability in Laboratory Medicine (JCTLM) listed RMPs (NRMeth 57 and NRMeth 8) was assessed, revealing excellent agreement. This RMP allows for highly sensitive and reproducible determination of cortisol. The performance of the RMP facilitates the standardization of routine assays and ensures traceability in the measurement of individual patient samples.
CRIS-Team Scopus Importer:2025-02-28
Keywords: cortisol; isotope dilution-liquid chromatography-tandem mass spectrometry; qNMR characterization; reference measurement procedure; SI units; traceability